2013
DOI: 10.1002/marc.201300618
|View full text |Cite
|
Sign up to set email alerts
|

Brush‐First Synthesis of Core‐Photodegradable Miktoarm Star Polymers via ROMP: Towards Photoresponsive Self‐Assemblies

Abstract: This report describes the synthesis of miktoarm brush-arm star polymers (BASPs) from branched and linear norbornene-terminated macromonomers (MMs) via the brush-first ring-opening metathesis polymerization (ROMP) method. First, a polystyrene (PS)-branch-poly(lactic acid) (PLA) MM is synthesized via a combination of atom transfer radical polymerization (ATRP), tin(II)-mediated ring opening polymerization, and copper-catalyzed azide-alkyne cycloaddition reactions. Graft-through ROMP of this MM followed by in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…Johnson et al developed a series of bottlebrush star polymers and copolymers as degradable drug carriers using a two-step synthesis approach [134][135][136][137] (Fig 14). The approach involves the preparation of living, end-functional bottlebrush arms by ROMP that are then coupled in a second reaction step with bis-norbornene crosslinker.…”
Section: Bottlebrush Assemblies In Solution For Delivery and Interfacmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al developed a series of bottlebrush star polymers and copolymers as degradable drug carriers using a two-step synthesis approach [134][135][136][137] (Fig 14). The approach involves the preparation of living, end-functional bottlebrush arms by ROMP that are then coupled in a second reaction step with bis-norbornene crosslinker.…”
Section: Bottlebrush Assemblies In Solution For Delivery and Interfacmentioning
confidence: 99%
“…In another study using the brushfirst approach, Johnson et al demonstrated the preparation of mikto-arm bottlebrush star polymers. Analysis by TEM showed the intramolecular phase separation of the various polymer arms to form Janus nanoparticles 135 .…”
Section: Bottlebrush Assemblies In Solution For Delivery and Interfacmentioning
confidence: 99%
“…6,7 The remarkable efficiency and functional group tolerance of ROMP 8 enables the benchtop synthesis 7 of diversely functionalized BASPs within hours. We have used the brush-first ROMP method to prepare degradable BASPs with various sizes and corona compositions, including multidrug-loaded poly(ethylene glycol) (PEG)-based BASPs, 9 two- and three-miktoarm BASPs, 10 and chloride-functional BASPs 11 for subsequent azide exchange and copper-catalyzed azide–alkyne cycloaddition (CuAAC) “click” 1214 chemistry.…”
mentioning
confidence: 99%
“…31,34 The conditions for the rst and the third ROMPs with NBE (4 and 15 minutes, respectively) were unchanged, because the NBE consumption should be completed based on our previous study. 31 The results are summarised in 26,27); it becomes more difficult to control the molecular weights (as well as to obtain the reproducibility).…”
mentioning
confidence: 99%